Humoral response after a fourth dose of SARS-CoV-2 vaccine in immunocompromised patients. Results of a systematic review - Silvia Martinelli; Domenico Pascucci; Domenico Pascucci; Patrizia Laurenti; Patrizia Laurenti (Frontiers Media S.A., 2023)
Background and objectiveThe fourth dose the COVID-19 vaccine was first proposed to immunocompromised patients. The aim of the article is to systematically review the literature and report the humoral response and outcomes after the fourth dose administration in people with impaired immune system.MethodsPublished studies on the humoral response, efficacy and safety of the fourth dose of the COVID-19 vaccine were analyzed in various settings of immunocompromised patients. We conducted systematic searches of PubMed, Cochrane Library and WHO COVID-19 Research Database for series published through January 31, 2023, using the search terms "fourth dose" or "second booster" or "4th dose" and "Coronavirus" or "COVID-19" or "SARS-CoV-2." All articles were selected according to the PRISMA guidelines.ResultsA total of 24 articles including 2,838 patients were comprised in the systematic review. All the studies involved immunocompromised patients, including solid organ transplant recipients, patients with autoimmune rheumatic disease, patients with human immunodeficiency virus (HIV) and patients with blood cancers or diseases. Almost all patients received BNT162b2 or mRNA-1273 as fourth dose. All the studies demonstrated the increase of antibody titers after the fourth dose, both in patients who had a serological strong response and in those who had a weak response after the third dose. No serious adverse events after the 4th dose have been reported by 13 studies. COVID-19 infection after the fourth dose ranged from 0 to 21%.ConclusionThe present review highlights the importance of the fourth dose of covid-19 vaccines for immunocompromised patients. Across the included studies, a fourth dose was associated with improved seroconversion and antibody titer levels. In particular, a fourth dose was associated with increasing immunogenicity in organ transplant recipients and patients with hematological cancers, with a very low rate of serious side effects.